2021
DOI: 10.1073/pnas.2011379118
|View full text |Cite|
|
Sign up to set email alerts
|

The conserved autoimmune-disease risk geneTMEM39Aregulates lysosome dynamics

Abstract: TMEM39A encodes an evolutionarily conserved transmembrane protein and carries single-nucleotide polymorphisms associated with increased risk of major human autoimmune diseases, including multiple sclerosis. The exact cellular function of TMEM39A remains not well understood. Here, we report that TMEM-39, the sole Caenorhabditis elegans (C. elegans) ortholog of TMEM39A, regulates lysosome distribution and accumulation. Elimination of tmem-39 leads to lysosome tubularization and reduced lysosome mobility, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
(52 reference statements)
1
6
0
Order By: Relevance
“…A phylogenetic tree was generated for the TMEM39 proteins of species, including human ( Homo sapiens ), chicken ( Gallus gallus ), zebrafish, fruit fly ( Drosophila melanogaster ), and C. elegans . Consistent with the previous report [ 46 ], the clade of vertebrate TMEM39B was clearly separated from that composed of vertebrate TMEM39A and invertebrate TMEM39 ( Figure 1 B). Furthermore, a sequence alignment analysis revealed that the sequence identity among TMEM39A or TMEM39B from different species was significantly higher than that between TMEM39A and TMEM39B from the same species ( Figure 1 C), suggesting a considerable functional differentiation between these two paralogs.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…A phylogenetic tree was generated for the TMEM39 proteins of species, including human ( Homo sapiens ), chicken ( Gallus gallus ), zebrafish, fruit fly ( Drosophila melanogaster ), and C. elegans . Consistent with the previous report [ 46 ], the clade of vertebrate TMEM39B was clearly separated from that composed of vertebrate TMEM39A and invertebrate TMEM39 ( Figure 1 B). Furthermore, a sequence alignment analysis revealed that the sequence identity among TMEM39A or TMEM39B from different species was significantly higher than that between TMEM39A and TMEM39B from the same species ( Figure 1 C), suggesting a considerable functional differentiation between these two paralogs.…”
Section: Resultssupporting
confidence: 92%
“…An ER-localized transmembrane protein, TMEM39A, was previously reported to regulate both ER stress response and autophagy [ 44 , 45 ]. TMEM39A also plays functions independent of ER stress response and autophagy, such as mediating collagen secretion [ 44 ], regulating lysosome distribution, and lysosome-associated signaling [ 46 ]. Genetic variants in the human TMEM39A gene are related to multiple autoimmune diseases [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the FCCP altered the mitochondrial pattern that formed round shape morphology, we did not observe recruitment of the mCherry::PDR-1 onto mitochondria despite its dynamic expression pattern in both standard and stressed conditions; see Figure 1A , and Supplementary Video 1 and 2 in Extended data 33 . To determine the subcellular localization of the mCherry::PDR-1 foci we crossed the dmaIs48 transgene with the GFP reporter for autophagosome adIs2122(lgg-1p::GFP::lgg-1) 34 and GFP(Venus) reporter for lysosome dmaIs58(rpl-28p::lmp-1::Venus) 35 . The confocal microscopy showed that the mCherry foci colocalize with both (LC3, GABARAP and GATE-16 family) and LMP-1 (LAMP (lysosome-associated membrane protein) homolog) reporters indicating that mCherry::PDR-1 is targeted to autophagosome-lysosome compartments ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…Co-immunoprecipitation has shown that DYNC1I2, or dynein cytoplasmic 1 intermediate chain 2, interacts with TMEM39A in mammalian cells. TMEM39A is an evolutionarily conserved protein involved in promoting proper lysosome positioning and accumulation, which are important for regulation of mTOR signaling, autophagy initiation, and immune-cell responses under a variety of physiological and pathological conditions (10). Changes in DYNC1I2 expression may be key to inducing immune responses in NB.…”
Section: Discussionmentioning
confidence: 99%